An intervention to train group exercise class instructors to adopt a motivationally adaptive communication style: a quasi-experimental study protocol - Hancox, Jennie; Quested, Eleanor; Thogersen-Ntoumani, Cecilie; Ntoumanis, Nikos (2015)
Introduction: According to self-determination theory (SDT), individuals in position of authority can have a powerful impact on the motivation of the individuals they instruct via the type of communication style they use. This paper describes (a) the rationale for and development of an SDT-based motivation communication training package for group exercise instructors and (b) the design and protocol for an intervention study to evaluate the implementation of this intervention. Methods and analysis: Fifty indoor cycling class instructors will be assigned to either an intervention group (n = 25) or a control group (n = 25). Over a 10-week period, instructors in the intervention group will complete a multiphase SDT-based communication training programme. The evaluation package will comprise qualitative and quantitative assessments of the motivationally relevant features of the class environment as well as motivation and well-being variables, undertaken by both exercise class members and instructors. Baseline quantitative data collection will take place up to one month prior to the start of the intervention and be re-administered within one month following the end of the intervention period. Quantitative data will be analysed using multilevel growth modelling. Follow-up semi-structured interviews with instructors and exercise class members will be conducted four to six weeks following the end of the intervention to explore perceptions of the training programme. All interviews will be analysed using inductive thematic analysis. Ethics and dissemination: The study has been granted ethical approval from Curtin University Ethics Board. The findings of the study will be disseminated through peer-reviewed journals and conference presentations.